2021
DOI: 10.1186/s12877-020-01969-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between medication or alcohol use and the incidence of frailty: a retrospective cohort study

Abstract: Background Understanding potentially modifiable factors that influence the risk of frailty is a key concern for the management of this urgent contemporary public health challenge. This study evaluates the association between the use of various medications or alcohol and the incidence of frailty among older adults. Methods This study was a retrospective cohort study on older adults (≥ 65 years) using data from the longitudinal Survey of Health, Agei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The effects of alcohol consumption on human health have always been hotly debated over the past decades without a consistent conclusion. Most of the previous studies have suggested that moderate alcohol use was associated with a decreased risk of frailty 34–36. One study showed that the Mediterranean drinking pattern, but not regular drinking, confers reduced frailty risk (OR=0.68) compared with non-drinkers in older adults 37.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of alcohol consumption on human health have always been hotly debated over the past decades without a consistent conclusion. Most of the previous studies have suggested that moderate alcohol use was associated with a decreased risk of frailty 34–36. One study showed that the Mediterranean drinking pattern, but not regular drinking, confers reduced frailty risk (OR=0.68) compared with non-drinkers in older adults 37.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior studies, the OR of the standardized activity diversity indicators with respect to the incidence of frailty or pre-frailty during study follow-up was presumed to be 1.5 ( 17 ). In contrast, the predicted incidence of frailty or pre-frailty was presumed to be 0.34 ( 26 ). Given an α of 0.05 and a targeted statistical power of 0.80, the minimum target sample size necessary within this study was n = 179.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was used to record medical history and number of medications taken. It requested information on the following conditions that have been linked to frailty: heart disease [26], osteoporosis [27], chronic obstructive pulmonary disease [28], knee osteoarthritis [29], anemia [30], depression [31], number of chronic diseases [32], Alzheimer's disease [33], chronic kidney disease [34], rheumatoid arthritis [35], Parkinson's disease [36], and stroke [36].…”
Section: Medical Interviewsmentioning
confidence: 99%